Implementation of Fish Feed Pellet Making Machine for Freshwater Fish Farming Groups in RW 04 Jatibening Baru Village, Bekasi City - Daisman P. B. Aji; Tono Sukarnoto; Pudji Astuti (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
The partners in this Community Service Program (PkM) are a group of freshwater fish cultivators in RW 04 Jatibening Baru Village, Bekasi City. Two main problems for partners are: 1. the high cost of fish feed so that business profits are not maximized and 2. business management that is not yet optimal. The purpose of this PkM activity is to apply appropriate technology for fish feed pellet machines as a result of faculty members’ research to benefit partners. The implementation method for this PkM is: The first stage is to collect data on the need for the number of fish feed pellets from partners, which then determines the type of pellet maker that is most suitable and then manufactures the pellet maker. The next stage is conducting training to partners in making fish feed pellets and business management with the canvas business model. By carrying out this service activity, it can be concluded that: 1. partners are able to reduce the cost of fish feed by 50%, 2. partners are able to make nutritional compositions for fish feed, and 3. partners understand the basics of the canvas business model in business management.